Sexual restiveness and colouration between partial diallel cross of genetically improved farmed tilapia 'GIFT' and UPM red tilapia - Nwachi, Oster F.; Esa, Yuzine; Christianus, Annie; Kamarudin, Salleh M. (Hashemite University, Deanship of Research and Higher Studies, 2020)
The effect of colouration, number of days for reproductive success and female preference for mating between 2 Cichlids: ‘Genetically Modified Farm Tilapia’ (GIFT) and UPM red tilapia were examined. A total of 24 female and 12 male homozygous stock of each of UPM red tilapia and GIFT were selected, They were paired in one ton tank and labelled as: (T1) at a ratio of 4:2 GIFT female X GIFT male (G x G), T2 UPM red tilapia female X GIFT male (U x G), T3 UPM red tilapia female X UPM red tilapia male (U x U) and T4 GIFT female X UPM red tilapia male (G x U) in triplicates. The experimental units were in triplicates and the trial was conducted at four separate times using the same broodstock. The number of days for reproductive successful varied from 14.2 days for T1 to 14.72 days for T3 with T4 having a longer period at 21.93 days. The mean highest value of swim-up recorded were 154.65 for T2, an indication that female fish shows affinity to the male fish of same colour with a level of preference to male of novel colouration compared to wild type of male.